Ice Dynamics and Morphological Changes During Proglacial Lake Development at Exploradores Glacier, Patagonia - Irarrazaval, Inigo; Dussaillant, Alejandro; Vivero, Sebastián; Iribarren-Anacona, Pablo; Mariethoz, Gregoire (Frontiers in Earth Science, 2022)
Proglacial lakes are ubiquitous features formed during deglaciarization and are currently increasing in number in Patagonia and elsewhere. Proglacial lakes can affect glacier dynamics, catchment hydrology and have the potential to cause glacial lake outburst floods. Therefore, monitoring the onset and development of proglacial lake formation is relevant to understand glacial processes and anticipate glacier response to climate change. In this study, we integrate geomorphological and ice-dynamic information to assess proglacial lake development in Exploradores Glacier, Chilean Patagonia. We monitor recent spatial and temporal changes in the lower trunk of Exploradores Glacier (10 km2) to provide a twenty-year observation record by combining eight uncrewed aerial vehicles (UAV) surveys between 2019–2020, with high-medium resolution satellite imagery (Rapid Eye and Landsat) between 2000 – 2018. We use feature tracking techniques, digital surface elevation model analysis and field data to create a multi-temporal scale (inter-annual and seasonal) and a multi-spatial (cm to km) data set. Our analysis shows that surface velocity overall trend has not changed over the last twenty years and that surface velocity near the terminus is significant (< 10 ma-1). Moreover, an exceptional advance over moraine deposits was detected. We also found low downwasting rates (> 0.5 m a-1) close to the glacier terminus which are attributed to sufficient ice flux and the insulation effect of the debris-covered surface. However, hundreds of supraglacial ponds were observed and are currently coalescing and expanding by ice-cliff backwasting favoring glacier disintegration. Lastly, it was found that calving losses at the east marginal lake equaled ice-flux input into the lake for the UAV monitored period. This study contributes to a better understanding of glacial lake dynamics during proglacial lake development, and our results may help ice modelling efforts to predict glacier response to future climate scenarios.